Efektivitas Penerapan Model Pembelajaran Logan Avenue Problem Solving -Heuristik Terhadap Pengetahuan Prosedural - Dassa, Awi; Thalib, Ahmad; Hardiana, Andi Sri (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
This research is to determine the effectiveness of implementation LAPS-Heuristic learning model in students grade VIII one ofSMP Negeri at Wajo regency with criteria,procedural knowledge, student activities and student responses.. The data were collected using initial knowledge test (pretest) at the first meeting and procedural knowledge test (posttest) at the final meeting, learning feasibility observation sheets, student activity observation sheets, and student’s response questionnaire.Research result descriptively obtained 1) Improvement of learning achievement in terms of normalized gain score obtained an average 0.6704 with standard deviation 0.21822, 2) Learning feasibility was done very well with average 3.85, 3) The results of student activity observation is in average percentage 95%, and 4) The increase of student’s procedural knowledge is reviewed through normalized gain score 0.6704 is in the medium category. Inferentially obtained 1) Hypothesis test for procedural knowledge obtained value of ttable = 2.080 with value α = 0,05 and tcount = 20,761, and 2) Hypothesis test for normalized gain obtained tcount= 14,409. Based on the results, LAPS-Heuristic learning model is effective to implement in mathematics learning on the subject of tangent line to two circles.